KOORDINASI PENERTIBAN PELABUHAN ILLEGAL DI KOTA SELATPANJANG KABUPATEN KEPULAUAN MERANTI - Mhd. Mulyawan; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Meranti district has a current Marine transport and ports are quite dense Karenamerupakan archipelago and adjacent to the neighboring countries, namely Malaysia and Singapore, where trade flows both countries is also high. Particularly in the Strait long as the capital city has a harbor district in addition to the official in many aquatic activities from ship berthing activities, Decrease Passenger and unloading is done at the port of unauthorized or illegal. So that illegal goods into the Selatpanjang suspected due to a number of ports in the region to be a place of loading and unloading the goods illegally. During this activity illegal port was rarely manifest monitoring of related parties.The problem in this research is; how to coordinate policing illegal port in the city district Selatpanjang Meranti?. What is inhibiting coordination of policing illegal port in Selatpanjang City Meranti district?The method used in this research is qualitative research methods. Data collection techniques in research, interview, search documentation, observation. Source of data in this study are primary data and secondary data.Based on the results of research conducted that guidance by the Department of Transportation, Communications and Informatics through empowerment conducted by the Department of Transportation, Communications and Informatics through awareness by holding seminars by inviting all district head, entrepreneurs sea transport, as the city of Selatpanjang Monitoring conducted by the Department of Transportation, Communications and Informatics in monitoring by involving municipal civil service police Unit directly against illegal port. Factors hindering the Department of Transportation, Communications and Informatics in fostering human resources are inadequate in fostering and monitoring, as the Department of Transportation, Communications and Information only have 14 people who served in fostering and supervision. Lowpublic awareness of government regulation on the importance of using the ports that have been authorized.Keywords: Coordination, Control, Port Illegal